2001
DOI: 10.1089/152460901300039584
|View full text |Cite
|
Sign up to set email alerts
|

Rural Physicians' Perspectives on Cervical and Breast Cancer Screening: A Gender-Based Analysis

Abstract: Several studies highlight the role of physicians in determining cervical and breast cancer screening rates, and some urban studies report higher screening rates by female physicians. Rural women in North America remain underscreened for breast and cervical cancers. This survey was conducted to determine if there were significant gender differences in practices and perceptions of barriers to breast and cervical cancer screening among rural family physicians in Ontario, Canada. One hundred ninety-one family phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 17 publications
1
19
0
3
Order By: Relevance
“…These poor experiences might deter their participation in future Pap screenings. Further, our results confirm that both Asian American and nonHispanic White women are more likely to undertake Pap screening when their providers are females (20,21).…”
Section: Cancer Epidemiology Biomarkers and Preventionsupporting
confidence: 72%
“…These poor experiences might deter their participation in future Pap screenings. Further, our results confirm that both Asian American and nonHispanic White women are more likely to undertake Pap screening when their providers are females (20,21).…”
Section: Cancer Epidemiology Biomarkers and Preventionsupporting
confidence: 72%
“…However, an analysis examining language concordance with Chinese American providers and mammography screening showed that language concordance with Chinese female providers was positively associated with screening [23]. Additional analysis from this study supports the key role of the provider's gender: having Chinese and non-Chinese female physicians were associated with higher rates of breast and cervical cancer screening in the US and Vancouver [48][49][50][51], while women with Chinese male physicians had the lowest screening rates. Of note, a majority of Chinese women in Vancouver, and significantly fewer in Seattle, reported that they had a Chinese male physician.…”
Section: Discussionmentioning
confidence: 58%
“…In addition to tailored education at the community level to reach those outside the medical care setting, healthcare providers influence patients' breast cancer screening behavior (20). In our study, SA women who ever had a periodic health examination were more likely to have a CBE but only 41% of all the participants ever had a routine physical exam.…”
Section: Discussionmentioning
confidence: 73%